2013
DOI: 10.1088/1367-2630/15/6/065008
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a coherent quantum memory for propagating microwave photons

Abstract: We describe a multi-mode quantum memory for propagating microwave photons that combines a solid-state spin ensemble resonantly coupled to a frequency tunable single-mode microwave cavity. We first show that high efficiency mapping of the quantum state transported by a free photon to the spin ensemble is possible both for strong and weak coupling between the cavity mode and the spin ensemble. We also show that even in the weak coupling limit unit efficiency and faithful retrieval can be obtained through time re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
84
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 52 publications
(69 reference statements)
0
84
0
2
Order By: Relevance
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…Such RE doped crystals are currently at the forefront of quantum communication research, where many thrilling achievements such as the demonstration of a quantum memory at the optical telecom C-band [13], high efficiency storage of optical photons [14], generation of entanglement between two RE doped crystals [15] and quantum teleportation between a telecom O-band photon (1.34 µm) and a RE doped crystal [16] have been reported. Also, RE doped crystals are considered to have a great potential as a multimode optical memory element in a future quantum repeater technology [17], and storage and retrieval of 64 temporal optical modes at the single photon level has been demonstrated [18].A crucial step towards the development of a microwave to optical interface requires highly efficient reversible mapping of temporal microwave modes into the rareearth spin ensemble at a power level corresponding to a single microwave photon [19]. In that respect, circuit Quantum Electrodynamics (QED) with RE doped crystals at the femtowatt power level and at milli-Kelvin temperatures presents a first step towards the implementation of a quantum memory [20,21].…”
mentioning
confidence: 99%
“…A crucial step towards the development of a microwave to optical interface requires highly efficient reversible mapping of temporal microwave modes into the rareearth spin ensemble at a power level corresponding to a single microwave photon [19]. In that respect, circuit Quantum Electrodynamics (QED) with RE doped crystals at the femtowatt power level and at milli-Kelvin temperatures presents a first step towards the implementation of a quantum memory [20,21].…”
mentioning
confidence: 99%
“…A quantum memory based on these RE elements can be very attractive for quantum communication between qubits of different physical nature [22]. Particularly in the case of SC qubits, the RE spin ensemble is expected to act as a coherent and reversible quantum converter between the optical domain and the microwave frequency band [23][24][25].The research on microwave quantum memories has started few years ago and is primarily focused on circuit QED experiments with electronic spin ensembles of nitrogen vacancies (NV) in diamond. The strong coupling of spins to as well as the full hybrid quantum architecture has recently been demonstrated [30,31].…”
mentioning
confidence: 99%
“…A quantum memory based on these RE elements can be very attractive for quantum communication between qubits of different physical nature [22]. Particularly in the case of SC qubits, the RE spin ensemble is expected to act as a coherent and reversible quantum converter between the optical domain and the microwave frequency band [23][24][25].…”
mentioning
confidence: 99%